(untitled) (Applied Biological Research, 2013)
Current research was designed to evaluate the prophylactic and therapeutic potential of garlic (Allium sativum) aqueous extracts in Schistosoma haematobium infection, using immuno-suppressed guinea pigs as animal model. Twenty four infected male guinea pigs were divided into various groups that were treated with A. sativum extracts over different periods, praziquantel treated group and control. Eggs recovered in various groups were counted and recorded. A substantial reduction in egg load of S. haematobium was observed in A. sativum extract-treated and praziquantel treated groups in comparison to untreated control. Further, praziquantel and sativum extract treatments significantly reduced worm burden. S. haematobium infection was established in guinea pigs under controlled immunosuppression. The study suggests that A. sativum aqueous extract is a convenient prophylactic and promising therapeutic agent for the control of S. haematobium infection.